Factibilidad para la creación de una empresa productora y comercializadora de abonos orgánicos de origen de palma aceitera (Elaeis guineensis jacqk) en el cantón Quevedo, año 2015 - Torres Briones, Segunda Cristina (2015)
The present investigation is carried out it with the purpose of determining the feasibility for the creation of a company producer and comercializadora of organic payments of origin of palm oil bottle (Elaeis Guineensis Jacqk) in the Canton Quevedo county of The Ríos, for that which was identified the offer and demand through the market study, the convenient requirements were obtained for the creation of the company in the sector, by means of the technical study and the profitability of the investment was determined through the financial study. The market study executed it to him in the canton Quevedo, county of The Ríos, for its effect the survey technique was implemented, directed to a sample of 595 producers and 1 interviews. To obtain the most convenient requirements for the creation of a company producer and comercializadora of organic payments of origin of palm oil bottle (Elaeis Guineensis Jacqk) in the area, the technical study was implemented where was detailed the size, localization, engineering of the project. The profitability of the investment of the project settled down it, implemented the economic and financial study, for that which the fixed and variable costs were calculated, taking into account the matter prevails and the resources that are needed for this process, settled down the VAN and the TIR, verifying the utility that generates the business, considering it profitable and feasible. According to the market study, he/she settled down that 100% of the interviewed producers accepts the creation of a company producer and comercializadora of organic payments of origin of palm oil bottle (Elaeis Guineensis Jacqk) in the canton Quevedo, reason why offered the opportunity to contribute to the development economic partner of the agricultural sector, to generate work sources, satisfying the demand and obtaining more benefits for the growth of the business. The net current value (they GO), obtained it was of $10.872, 46, this value related with the TIR 34, 6%, demonstrates the profitability of the business, reason why it becomes feasible and profitable the creation of the company producer and comercializadora of organic payments of origin of palm oil bottle (Elaeis Guineensis Jacqk) of the canton Quevedo, was also determined that the investment will recover in a 5 year-old approximate period. He/she corresponds to meditate on the results reached in the technical, economic study and made financier, to create the company, it is important to satisfy the demand of the sector establishing a company producer and comercializadora of organic payments of origin of palm oil bottle (Elaeis Guineensis Jacqk) of the canton Quevedo.